2023
DOI: 10.3389/fenvs.2023.1099030
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: Reservoirs facilitate enhanced interactions among generalist and rheophilic fish species in tributaries

Abstract: Most lotic ecosystems have been heavily modified in recent centuries to serve human needs, for example, by building dams to form reservoirs. However, reservoirs have major impacts on freshwater ecosystem functions and severely affect rheophilic fishes. The aim of this review is to gather evidence that aside from direct habitat size reductions due to reservoir construction, competition for food and space and predation from generalist fishes affect rheophilic community compositions in tributaries (river/stream n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 219 publications
(229 reference statements)
1
6
0
Order By: Relevance
“…In our study, however, the body temperature of all observed fish individuals across seasons was comparable, indicating that fish in the reservoir occupied environments with similar temperature conditions as those in the tributary. The findings support the view that natively riverine species perform similar behavioural schema in reservoirs, for example, occupation of temperature niche, as in the riverine environment (Fernando & Holčík, 1991; Šmejkal et al, 2023). However, our data do not permit us to determine the reason for the modest difference between the winter body temperatures of individuals from the reservoir and those from the tributary.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In our study, however, the body temperature of all observed fish individuals across seasons was comparable, indicating that fish in the reservoir occupied environments with similar temperature conditions as those in the tributary. The findings support the view that natively riverine species perform similar behavioural schema in reservoirs, for example, occupation of temperature niche, as in the riverine environment (Fernando & Holčík, 1991; Šmejkal et al, 2023). However, our data do not permit us to determine the reason for the modest difference between the winter body temperatures of individuals from the reservoir and those from the tributary.…”
Section: Discussionsupporting
confidence: 82%
“…The drive to find suitable feeding habitats corresponds with the findings that, compared to stationary individuals, migratory individuals had lower somatic conditions (Brodersen et al, 2019; Grift et al, 2001). Moreover, reservoirs may represent a more competitive environment with lower food availability (Šmejkal et al, 2023) than the inflow area of tributaries and/or structured habitats within tributaries (Benda et al, 2004; Bouska et al, 2023; Pander & Geist, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, common carp from pond aquaculture is commonly stocked into fishing grounds in rivers, which emphasises the importance of fish stock control (Kalous et al ., 2018). The landscapes filled with ponds and reservoirs are more susceptible to fish invasions (Šmejkal et al ., 2023), as has also been shown by the spread of IAS topmouth gudgeon and gibel carp ( Carassius gibelio ) (Lusk et al ., 2010).…”
Section: Brief Communicationmentioning
confidence: 99%